Effectiveness of four components of mindfulness based on acceptance and commitment (MAC) on cognitive and physical anxiety of female athletes during the COVID-19 pandemic - Mohsen Akbarpour Beni; Mobina Mirgalouye Bayat; Melinaz Rahman Gholhaki; Mahdi Fahimi (Turkish Journal of Kinesiology, 2023)
The aim of the study was to test whether mindfulness based acceptance/commitment (MAC) could reduce cognitive-physical anxiety of female athletes to an active control group. This study was a semi-experimental design, Randomized controlled trail with an 8 week (16 sessions, 90 min each) and the active control group. Fifty female fitness athletes (Mage=25.14; SD=1.5) were randomly assigned either to MAC intervention or active control condition. All participations completed Kentucky Mindfulness Inventory (KIMS) and Smith Anxiety Inventory. MANOVA analyses were used to assess time by interactions. Significant value by group interaction effects were found for all outcomes. In the MAC group, Observational and Descriptive Aspects of Mindfulness are more effective in reducing cognitive anxiety rather than physical anxiety. In the active control group, the outcomes remained relatively stable. The present finding suggest that among female aerobic athletics, a MAC intervention has the potential to reduce cognitive and physical anxiety by increase observational and descriptive aspects more than Act with awareness, Accept without judgment aspects. The MAC model is one of the best systematic approaches to mindfulness training in sport psychology and has positive impact on performance, as well as the overall development of mental health and well-being.